Systematic Literature Review: Factors in Fruit Purchase and Consumption Decisions in Indonesia - Rizky Lutfi Suprabowo; Oktarina Nur Widyanti; Ila Fadila; Nurul Khotimah; Risman Ramadwika (Jambura Agribusiness Journal, 2026)
Fruit consumption plays an important role in maintaining public healthhowever, the level of fruit consumption in Indonesia remains relatively low compared to the standards recommended by the Food and Agriculture Organization (FAO). This situation highlights the need for academic investigation to understand the factors influencing consumers’ fruit purchasing decisions. This study aims to analyze the determinants of fruit purchasing behavior in Indonesia using a Systematic Literature Review (SLR) approach. The research data were obtained from 45 scientific articles published between 2021 and 2025. The article identification and retrieval process was conducted using the Publish or Perish software, while VOSviewer was utilized to perform bibliometric visualization.The results indicate that price and product quality are the most dominant factors influencing fruit purchasing decisions. These variables are followed by other determinants such as income level, taste preferences, promotion, and sales location, which also contribute to consumer decision-making. Bibliometric cluster analysis reveals three major research themes in the existing literature: (1) product attributes and consumer preferences, (2) the role of the marketing mix and consumer demand dynamics, and (3) the relationship between price, product quality, and external influences. Demographic variables such as age, education, and occupation demonstrate varying levels of influence on purchasing behavior. Psychological aspects, consumer satisfaction, and cultural factors also contribute to purchasing decisions, although their influence is less dominant than that of economic and product-related variables. The study concludes that fruit purchasing decisions in Indonesia are multidimensional, shaped by the interaction between internal consumer factors and external market conditions. Based on these findings, the study recommends the development of adaptive agribusiness strategies, particularly through integrated marketing approaches and digital promotion, that combine competitive pricing, product quality improvement, and alignment with consumer preferences to increase fruit consumption in Indonesia sustainably.